Consensus on Indications for Hematopoietic Stem Cell Transplantation in Pediatrics. Update 2020: Central Nervous System Tumors and Retinoblastoma : V Meeting of Brazilian Guidelines on Hematopoietic Stem Cell Transplantation of the Brazilian Society of Bone Marrow Transplantation - SBTMO - Galvao de Castro Junior, Claudio (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2021)
The indications for hematopoietic stem cell transplantation in solid tumors in children do not change a lot since our first Brazilian consensus publication in 2009. In this article, we are going to review indications to hematopoietic stem cell transplantation in solid tumors. For the consensus, a review was made using the most relevant articles, and a series of meetings was done to discuss the recommendations. In some indications, autologous transplantation is no longer used as a treatment option, however we chose to review these diseases and keep them as a non-recommendation. In this article we are going to review CNS tumors and retinoblastoma